2016
DOI: 10.3171/2015.3.jns142121
|View full text |Cite
|
Sign up to set email alerts
|

Ventricle wall dissection and vascular preservation with the pulsed water jet device: novel tissue dissector for flexible neuroendoscopic surgery

Abstract: OBJECT Neuroendoscopic surgery allows minimally invasive surgery, but lacks effective methods to control bleeding. Water jet dissection with continuous flow has been used in liver and kidney surgery since the 1980s, and is effective for tissue manipulation with vascular preservation, but involves some potential risks, such as elevation of intracranial pressure during application in the ventricles. The authors previously reported the efficacy of the actuator-driven pulsed water jet device (ADPJ) to dissect soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The needle‐free micro‐jet injectors have the advantage of controlled release to the depth of the dermis with a minimum and recoverable breach of the target. Primarily, the liquid jet preserves most of the blood vessels and immune network in the target, reducing bleeding, and keeping the disseminative mechanism intact (Kawaguchi et al, ; Nakagawa et al, ; Seto et al, ; Tominaga et al, ). The minimum breach of the target cells will improve the uptake of drug, enhancing the effectiveness of drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The needle‐free micro‐jet injectors have the advantage of controlled release to the depth of the dermis with a minimum and recoverable breach of the target. Primarily, the liquid jet preserves most of the blood vessels and immune network in the target, reducing bleeding, and keeping the disseminative mechanism intact (Kawaguchi et al, ; Nakagawa et al, ; Seto et al, ; Tominaga et al, ). The minimum breach of the target cells will improve the uptake of drug, enhancing the effectiveness of drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast, it uses a "pulsed" water jet that has the advantages of fine vessel preservation, no heat injury, and less water required for tissue dissection. 7,21,22 We previously reported an increased resection rate and functional maintenance in glioma and pituitary surgery with the preservation of fine vessels. [23][24][25] In addition to brain surgery, our group also applied the ADPJ for spinal cord, liver, kidney, gastrointestinal endoscopy, and retinal vascular surgery.…”
mentioning
confidence: 99%
“…2 This device was used for brain tumor resection and in neuroendoscopic surgery. [5][6][7] Passacantilli et al reported the usefulness of the 2-μ thulium laser for dissection and resection of intracranial meningioma. 8 We developed an ultrasonic microdissector to improve the cutting effect by application of ultrasonic vibration to the blade that can be used for fine cutting even fragile items such as a jellyroll cake and cream puffs at home.…”
Section: Discussionmentioning
confidence: 99%